A Flexible Sulfur‐Enriched Nitrogen Doped Multichannel Hollow Carbon Nanofibers Film for High Performance Sodium Storage. Issue 35 (5th August 2018) - Sun, Xizhen; Wang, Changlai; Gong, Yue; Gu, Lin; Chen, Qianwang; Yu, Yan
Abstract: Heteroatom doping is regarded as a promising method to enhance the sodium storage performance of carbon materials. In this work, a sulfur‐enriched N‐doped multichannel hollow carbon nanofiber (denoted as S‐NCNF) film is prepared through electrospinning technology and heat treatment with sublimed sulfur as the flexible anode for sodium ion batteries (NIBs). The S‐NCNF film displays outstanding electrochemical performance, particularly with a high rate capacity (132 mA h g −1 at the current density of 10 A g −1 ) and remarkable long cycling stability (reversible specific capacity of 187 mA h g −1 at 2 A g −1 over 2000 cycles). The improved sodium storage performance results from the unique 3D structure, abundant defects, and increased interlayer spacing of S‐NCNFs. The density functional theory calculations demonstrate that nitrogenous carbon nanofibers doping with sulfur could not only promote the adsorption of sodium but also favor electrons' transfer. This strategy has been demonstrated as a general process to design free‐standing carbon‐based thin film with other heteroatom doping. Abstract : A flexible sulfur‐enriched nitrogenous multichannel hollow carbon nanofibers (denoted as S‐NCNFs) film is prepared through electrospinning technology and heat treatment with sublimed sulfur. The film electrode exhibits excellent high rate capacity and prominent long cycling performance with Coulombic efficiency closing to 100%, showing that it is a promising anode material for sodium ion batteries.